2018
DOI: 10.1016/j.chest.2017.08.1163
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Trial of a Checklist for Endotracheal Intubation of Critically Ill Adults

Abstract: ClinicalTrials.gov; No.: NCT02497729; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 25 publications
(29 reference statements)
1
111
1
4
Order By: Relevance
“…In contrast, in two studies where PICL was the only study intervention, no beneficial effect could be demonstrated . A large multicentre study where patients were randomised to either checklist or no checklist, Janz et al could not detect any significant difference in the incidence of deoxygenation, hypotension nor first pass success rate . Nor could Conroy et al detect any improvement in complication metrics after institution of a PICL in an emergency department .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, in two studies where PICL was the only study intervention, no beneficial effect could be demonstrated . A large multicentre study where patients were randomised to either checklist or no checklist, Janz et al could not detect any significant difference in the incidence of deoxygenation, hypotension nor first pass success rate . Nor could Conroy et al detect any improvement in complication metrics after institution of a PICL in an emergency department .…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Kerrey et al reported a 17% decrease in the incidence of peri‐intubation desaturation following the introduction of an improvement initiative where PICL use was one of several interventions . In contrast, in two studies where PICL was the only study intervention, no beneficial effect could be demonstrated . A large multicentre study where patients were randomised to either checklist or no checklist, Janz et al could not detect any significant difference in the incidence of deoxygenation, hypotension nor first pass success rate .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation to this finding is that an OTI protocol is only a grade 2+ recommendations in French guidelines [7]. In addition, the usefulness of a checklist was challenged recently [25].…”
Section: Global Airway Managementmentioning
confidence: 99%
“…Under WIC regulations the research must involve no more than minimal risk, meaning that the probability and magnitude of harm or discomfort anticipated in the research is not greater than encountered in routine medical examination and testing (21 CFR 50.3[k]) . WIC has been utilized for many prospective comparative effectiveness investigations comparing standards of care, such as medical devices or clinical protocols . WIC trials have not generally been used for comparative drug investigations, such as randomized, blinded drug intervention trials.…”
mentioning
confidence: 99%